2008
DOI: 10.3928/01477447-20110525-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Accuracy of Acetabular Cup Orientation in CT-Free Navigated Total Hip Arthroplasty

Abstract: We have used the Orthopilot (Aesculap AG, Tuttlingen, Germany) computed tomography (CT)-free navigation system to ensure accurate and reproducible acetabular cup orientation. In this system, cup orientation is assessed with respect to bony configuration as determined by palpation of the anatomical landmarks (the bilateral anterosuperior iliac spines and the upper margin of the pubic symphysis). In this study, intraoperative cup orientation as presented by the OrthoPilot navigation system was compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
1
17
1
2
Order By: Relevance
“…Our results compare favorably with these previous studies, although only Fununkashi et al [19] (one patient with a discrepancy of > 5 0 degrees) and Dorr et al [12] (no outliers) reported outliers. In contrast to the previous authors [12,17-19], we documented similar differences but we have observed more frequent cup placements with a discrepancy of > 5 0 degrees.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results compare favorably with these previous studies, although only Fununkashi et al [19] (one patient with a discrepancy of > 5 0 degrees) and Dorr et al [12] (no outliers) reported outliers. In contrast to the previous authors [12,17-19], we documented similar differences but we have observed more frequent cup placements with a discrepancy of > 5 0 degrees.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the previous authors [12,17-19], we documented similar differences but we have observed more frequent cup placements with a discrepancy of > 5 0 degrees. It may therefore be more important to report on the numbers of outliers rather than documenting mean differences, ranges and standard deviations.…”
Section: Discussioncontrasting
confidence: 62%
“…The accuracy of the image-free THA cup navigation system has been assessed and reported in several clinical studies and satisfactory agreement between the intra-operative navigation results and the post-operative values obtained from X-rays have been reported. 11–15 In our previous studies, 7,8 we also reported satisfactory results with cup setting angle with the use of the image-free navigated THA. However, we did not look into stem AT and CA in our initial reports.…”
Section: Discussionmentioning
confidence: 64%
“…The effectiveness of this system in our clinical experience has been confirmed and reported in previous clinical studies. 79 However, this system is not equipped with a tool to evaluate and control torsion of the stem. Consequently, the stem AT was determined arbitrarily by the surgeon and, therefore, the resultant CA value in our navigated THA can vary.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have evaluated the clinical accuracy (deviation of implant orientation from preoperative planning to postoperative measurement) and measurement error (deviation of orientation from intraoperative final measurement by navigation system to postoperative measurement) of navigation systems [18,21,[24][25][26][27][28]. Although a CT-based 3D templating technique is generally used for postoperative implant measurement, those results included errors in the evaluation methods, of course.…”
Section: Discussionmentioning
confidence: 99%